2020
DOI: 10.1007/s00216-020-03018-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted screening workflows for gas chromatography–high-resolution mass spectrometry analysis and identification of biomagnifying contaminants in biota samples

Abstract: The health of key species in the Baltic region has been impaired by exposure to anthropogenic hazardous substances (AHSs), which accumulate in organisms and are transferred through food chains. There is, thus, a need for comprehensive characterization of the occurrence and accumulation of AHSs in the ecosystem. In this study, we use a non-target screening (NTS) approach for this purpose. A major challenge in NTS of biological samples is the removal of matrix components such as lipids that may interfere with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…were determined gravimetrically. 7 Bulk lipids were removed by high-resolution gel permeation chromatography (HR-GPC), as described in Table S2 . Contaminant fractions were collected, concentrated, and subjected to a second round of HR-GPC.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…were determined gravimetrically. 7 Bulk lipids were removed by high-resolution gel permeation chromatography (HR-GPC), as described in Table S2 . Contaminant fractions were collected, concentrated, and subjected to a second round of HR-GPC.…”
Section: Methodsmentioning
confidence: 99%
“…Contaminant fractions were collected, concentrated, and subjected to a second round of HR-GPC. Samples were further fractionated using a Florisil column ( Table S2 ), 7 and the first three fractions ( n -hexane, 15% dichloromethane in n -hexane, and 50% dichloromethane in n -hexane) were retained. Volumetric standard ( 13 C 12 –CB-188; 3 ng) was added to each fraction, and their volumes were reduced to 0.3 mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main reasons is that large-sample batch data processing of GCxGC-HRMS data is in its infancy. There are several levels of identification and verification steps needed for such a data-driven approach which were recently summarized by Stefanuto et al 1 and Schymanski et al 2 It is often concluded that the automation of non-target analysis and subsequent suspect-screening remains an elusive process. This process can be intricate due to small deviations in retention times, suboptimal peak shapes, intensive background, and the diversity of chromatographic features among samples (e.g., large qualitative differences between samples), which makes the development of an efficient approach for use with large batches of samples challenging.…”
Section: Introductionmentioning
confidence: 99%